Pengaruh Model Learning Cycle 5E dan Model Two Stay Two Stray Ditinjau Dari Kemampuan Awal terhadap Hasil Belajar IPA Siswa: The Effect of the Learning Cycle 5E Model and the Two Stay Two Stray Model in Terms of Initial Ability to Student Learning Outcomes in Science - Suwaji Suwaji; Syaiful Syaiful; M. Haris Efendi Hsb (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2019)
Students’ learning outcome on the national final exam in MTs Minhajul Ishlah school in the Tebo District is still low. To overcome the problem, researchers apply a learning model of Learning Cycle 5E and Two Stay Two Stray learning models. This study aims to determine the effect of the learning models on science learning outcomes by taking account student initial ability. The research took place in the MTs Minhajul Ishlah School in the Tebo District on the subject of solar system in the second semester of the 2018/2019 school year. This experiment research employs a Posttest-Only Control Design. The population in this study was all VII grade students in the MTs Minhajul Ishlah School. The sample in this study was taken randomly and the selected sample classes were class VIIA as experimental class I and VIIB as experimental class II while class VIIC served as a control class. Data were analyzed using Two-Way Anova. Based on the results of the post-test data analysis with a 95% confidence level, it can be concluded that there is a significant effect of the Learning Cycle 5E learning model and the Two Stay Two Stray models by considering the students initial abilities on theirscience learning outcome.